Physicochemical, Proximate, Heavy Metals and Antimicrobial Assessment of Few Selected Herbal Medicinal Products Consumed in Awka, Anambra State, Southeastern, Nigeria - Onyema Agu, Matthew; Dennis Onyema, Anayochukwu; Yakubu, Shedrach; Chibuike Sylvester, Onyima (Science Tech Group, 2025)
Traditional medicine remains the principal approach to healthcare in the third world, but knowledge about preparation methods, toxicological effects, and side effects is lacking. This study evaluates the quality of local herbal medicines in Awka, Anambra State, Southeastern, Nigeria by assessing the proximate composition, physicochemical, heavy metals, and antimicrobial efficacy of a few selected herbal medicines. The physiochemical analysis of herbal drugs revealed high acidity, except for the herbal medicine called ‘Evacuation’. The evaluated Herbal medicines are rich in alkaloids, flavonoids, tannins, phenol, and saponins but poor in protein, resin, steroid, and terpenoid. The concentrations of iron, chromium, and lead exceeded WHO/FAO limits. The Herbal medicines have lower zones of inhibition as compared to the 99 % efficacy inscription on the label. In the case of proximate composition, the herbal medicine ‘Super 7’ contains higher protein, fat, and ash content, while ‘Deep root’ has the highest fiber, ADC has the highest moisture, and Evacuation has the highest carbohydrate. Therefore, from a toxicological point of view, some of these herbal medicines may not be safe for consumption and they may pose health risks ranging from kidney failure, gastrointestinal disorder, dysentery, and cancer of the vital organs of the consumers due to the presence of toxic metals, high acidity, and imbalance in concentrations of the bioactive constituents.